Public awareness regarding the use and resistance of antibiotics: A cross-sectional study among Nepalese adults in Kathmandu valley - Deo, Satish Kumar; Rijal, Sita; K.C, Tulza (Journal of Kathmandu Medical College, 2018)
Background: Antibiotics are considered to be among the most commonly sold drug classes globally. Antibiotic resistance is a recognized public health issue at the local, national and global levels.Objectives: The aim of this study was to identify awareness of general public regarding the use and resistance of antibiotics.Methodology: A descriptive cross-sectional study was conducted in Kathmandu in November 2016 using a quantitative questionnaire among 120 adult people aged 20–60 years. Convenience sampling method was used and information on use of antibiotics and resistance was obtained using semi-structured questionnaire through interview method. Descriptive statistics was done to describe the respondent’s level of awareness regarding use of antibiotics and resistance.Results: Among the total respondents, majority had incorrect awareness as regards to action, reasons for using antibiotics, possible side effects of the antibiotic. Seventy one percent of the respondents had not heard about antibiotic resistance. The study finding showed that about 66.7% of the participants had inadequate awareness towards use and resistance of antibiotics.Conclusion: The findings demonstrate that the overall awareness on antibiotic use and resistance is poorly understood among our respondents. This information can be utilized in future educational and antibiotic resistance awareness raising campaigns.